Eksplorasi Bakteri Antagonis Asal Jaringan dan Rizosfer Tanaman Celosia argantea Untuk Menekan Pertumbuhan Fusarium sp. Secara In Vitro - Siti Shofiya Nasution; Alfi Saryanah (Jurnal Media Pertanian, 2023)
Fusarium sp. is a fungus causing serious disease in many plants. This study aims to explore antagonistic agents which potential to suppress Fusarium sp. in vitro. This research was conducted from October to December 2015 at Nematology laboratory, Department of Plant Protection, Bogor Agricultural University. The materials used in this study were Celosia argantea, 20% and 100% TSA media, sterile distilled water, 3% sodium hypochlorite (NaOCl). The tools used are laminar air fliw, autoclave, shaker, petridish. This candidate antagonist agent was isolated from the endophytic, phyllosphere, rhizosphere, and rhizoplane of Celosia argantea. The results of this study showed that the abundance of bacteria in the phyllosphere of C. argantea was higher than the rhizosphere, rhizoplane, and endophytes, but the diversity was higher in the rhizoplane. Bacterial isolates RP10 and RP 11 have potential as antagonistic agents against Fusarium sp.